2016
DOI: 10.1142/s0217751x16450421
|View full text |Cite
|
Sign up to set email alerts
|

Renormalisation group determination of scalar mass bounds in a simple Yukawa-model

Abstract: The scalar mass is determined in the simplest scalar-fermion Yukawa-model in the whole range of stability of the scalar potential. Two versions of the Functional Renormalisation Group (FRG) equations are solved, where also composite fermionic background is taken into account. The close agreement of the results with previous studies taking into account exclusively the effect of the scalar condensate, supports a rather small systematic truncation error of FRG due to the omission of higher dimensional operators.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Various incarnations of "functional renormalisation" are available [33][34][35][36][37] which, in combination with systematic approximations [38][39][40][41][42][43][44], give access to the relevant physics including at strong coupling. Recent applications of the methodology include models of particle physics [45][46][47], purely fermionic models [48], quantum gravity [49][50][51][52][53][54], and models in fractal or higher dimensions [55][56][57][58][59][60] The primary focus of this work will be on (φ 2 ) 3 d=3 scalar field theories in the limit of infinite N [61,62]. Our interest in this model is twofold: Firstly, the theory offers a rich spectrum of phenomena ranging from interacting ultraviolet fixed points with asymptotic safety to strongly interacting Wilson-Fisher fixed points, phase transitions and dimensional transmutation, and interaction-induced spontaneous breaking of scale invariance [63].…”
Section: Introductionmentioning
confidence: 99%
“…Various incarnations of "functional renormalisation" are available [33][34][35][36][37] which, in combination with systematic approximations [38][39][40][41][42][43][44], give access to the relevant physics including at strong coupling. Recent applications of the methodology include models of particle physics [45][46][47], purely fermionic models [48], quantum gravity [49][50][51][52][53][54], and models in fractal or higher dimensions [55][56][57][58][59][60] The primary focus of this work will be on (φ 2 ) 3 d=3 scalar field theories in the limit of infinite N [61,62]. Our interest in this model is twofold: Firstly, the theory offers a rich spectrum of phenomena ranging from interacting ultraviolet fixed points with asymptotic safety to strongly interacting Wilson-Fisher fixed points, phase transitions and dimensional transmutation, and interaction-induced spontaneous breaking of scale invariance [63].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, based on the functional RG [48][49][50][51] as well as nonperturbative lattice simulations [52][53][54][55][56], a lower Higgs mass bound emerges naturally from the RG flow itself and is primarily connected with a consistency condition on the bare action rather than with the stability of the effective Higgs potential which is a resulting long-range property. Moreover, it can be shown that higher-order operators at the standard-model cutoff scale can have a quantitative impact on the lower Higgs mass bound as well as the stability properties of the bare potential.…”
Section: Introductionmentioning
confidence: 99%
“…Our estimates based on a variety of model studies suggest that even Planck scale operators can induce a relaxation of the conventional lower bound on the order of 1% for the absolute stability bound. While we have considered here the influence of only one φ 6 -type operator as an example, similar features occur, for instance, upon the inclusion of higher-order fermionic operators [30,31] or mixed operators [32] as well as in theories with additional scalar fields, e.g., dark matter candidates [47]. Most of the quantitative studies so far have explored only initial conditions which are already sufficiently close to the Gaußian fixed point.…”
Section: Resultsmentioning
confidence: 93%
“…As a simple generalization, let us consider the next higher-order operator in the potential ∼ λ 3,Λ φ 6 . In fact, many further operators can be (and have been) studied; see, e.g., [30,31] for higher-order fermionic operators or [32] for mixed operators. The present simple φ 6 example suffices to illustrate an important point here.…”
Section: Higgs Mass Bounds As a Uv To Ir Mappingmentioning
confidence: 99%